Enhancing Antibiotic Stewardship Team (AST) Efforts in Decreasing Inappropriate Vancomycin Usage in Neutropenic Fever (NF) Patients through Unit Based Pharmacist Intervention. (4th October 2017) - Perreault, Sarah; Amin, Kejal; Daleo, Stephen; Nguyen, Michelle Nadeau; McManus, Dayna; Topal, Jeffrey; Malinis, Maricar
Abstract: Background: The Infectious Diseases Society of America and the National Comprehensive Cancer Network guidelines recommend adding vancomycin to the empiric treatment of NF in patients meeting specific criteria. After 48 hours, the guidelines recommend discontinuing vancomycin if resistant Gram-positive organisms are not identified. An analysis of vancomycin use for NF at our institution revealed 35% of patients had vancomycin discontinued appropriately at 48 hours. Based on these results, a vancomycin stewardship team defined criteria for continuation of vancomycin past 48 hours and increased surveillance of vancomycin usage through AST oversight. The objective of this study is to assess the incidence of vancomycin discontinuation at 48 hours with the new criteria of use and the addition of pharmacist led stewardship. Methods: This study included NF patients who were treated with an antipseudomonal β-lactam and vancomycin from January to April 2017. Criteria for vancomycin continuation beyond 48 hours included culture-documented Gram-positive infection, positive Methicillin Resistant S.aureus (MRSA) nasal swab with evidence of pneumonia, or hemodynamic instability due to septic shock. Patients who received aztreonam, or a single dose of vancomycin were excluded. Patient characteristics, previous MRSA infection, MRSA nasal swab collection and results, culture results, fever status, duration of vancomycin, rationale for continuation of vancomycin past 48 hours, re-initiation of vancomycin, and AST recommendations were collected. Results: Sixty-nine patients with 73 admissions were initiated on vancomycin for NF during the study period. Vancomycin was appropriately discontinued in 63% (46/73) compared with 35% (19/54) previously. An additional 8% (6/73) was discontinued between 48 and 72 hours, and 20% (15/73) was continued past 72 hours inappropriately. The most common reasons for continuation was lack of neutrophil recovery (5) and cellulitis (4). AST recommended discontinuation on 5 patients, all of which were accepted. Conclusion: Establishing criteria for vancomycin use along with pharmacist led antibiotic surveillance, AST, and provider education improved the use of vancomycin with the discontinuation rate increasing from 35% to 63%.( P = 0.002) Disclosures: All authors: No reported disclosures.